2023
DOI: 10.1038/s41419-023-05648-9
|View full text |Cite
|
Sign up to set email alerts
|

ASAP1 activates the IQGAP1/CDC42 pathway to promote tumor progression and chemotherapy resistance in gastric cancer

Abstract: Abnormal expression and remodeling of cytoskeletal regulatory proteins are important mechanisms for tumor development and chemotherapy resistance. This study systematically analyzed the relationship between differential expression of cytoskeleton genes and prognosis in gastric cancer (GC). We found the Arf GTP-activating protein ASAP1 plays a key role in cytoskeletal remodeling and prognosis in GC patients. Here we analyzed the expression level of ASAP1 in tissue microarrays carrying 564 GC tissues by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These findings agree with our observed reduction in cell proliferation from the MTT-based growth assays (Figure 1 C), and previous literature. 27 Later time points 7, 14 and 21 highlighted GOs related to GTPase-dependent regulation, transcription-related processes and serine/threonine kinase activity (Supplementary Figure S2 C). Given the KRAS-ARF6-downstream role of ASAP1, and regulation by the MAPK pathway, downregulation of GTPase activity is expected.…”
Section: Resultsmentioning
confidence: 99%
“…These findings agree with our observed reduction in cell proliferation from the MTT-based growth assays (Figure 1 C), and previous literature. 27 Later time points 7, 14 and 21 highlighted GOs related to GTPase-dependent regulation, transcription-related processes and serine/threonine kinase activity (Supplementary Figure S2 C). Given the KRAS-ARF6-downstream role of ASAP1, and regulation by the MAPK pathway, downregulation of GTPase activity is expected.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, studies have endeavored to explore new cancer treatments by identifying novel GC targets. In our prior research, ASAP1 overexpression was found to be correlated to the poorer overall survival of GC [ 14 , 15 ]. Therefore, we demonstrate that ASAP1 is overexpressed in GC cells compared to GES1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Junnila et al conducted expression analysis of ASAP1 and other genes in both GC and non-malignant GC tissues using affinity capture-based transcript analysis (TRAC assay), revealing differential expressed of ASAP1 between them [ 13 ]. Previous studies have shown that ASAP1 is significantly overexpressed in GC tissues, and is negatively correlated with disease-free survival time and overall survival time [ 14 , 15 ]. Therefore, further investigation is warranted to explore the potential anti-GC effect of ASAP1 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell division cycle 42 (CDC42), a key member of the Rho GTPase protein family, plays a role in various cellular functions, including cell proliferation, migration, invasion, and pseudopod formation [ 10 , 11 ]. CDC42 effector proteins (CEPs) are a group of effector proteins downstream of CDC42, comprising five members: CDC42EP1/2/3/4/5 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%